Note on the channel capacity of narrowband subliminal channels in one-way function - DONG Qing-kuan1; 2; LI Xiao-ping3 (Tongxin xuebao)
The channel capacity of narrowband subliminal channels in one-way function was studied to effectively evaluate the ability of subliminal channels to transmit subliminal messages. The definition of Kobara and Imai on the practical channel capacity of narrowband subliminal channels in information-theoretic view was analyzed and its limitation that the bit error ratio in one-time subliminal communication was not considered was pointed out. The bit error ratio is very important in one-time subliminal communication. A new method to calculate the size of the narrowband subliminal channels is presented to reduce the above limitation, which is very practical in applications.